Using EEG to study sensorimotor adaptation. (March 2022) - Reuter, Eva-Maria; Booms, Arthur; Leow, Li-Ann
Highlights: This is the first comprehensive overview of EEG in sensorimotor adaptation. We describe how EEG markers change with adaptation. We identify markers that are sensitive to the size of trajectory- or task errors. We review predictors of adaptation outcomes. We discuss latent effects of adaptation on attention. Abstract: Sensorimotor adaptation, or the capacity to flexibly adapt movements to changes in the body or the environment, is crucial to our ability to move efficiently in a dynamic world. The field of sensorimotor adaptation is replete with rigorous behavioural and computational methods, which support strong conceptual frameworks. An increasing number of studies have combined these methods with electroencephalography (EEG) to unveil insights into the neural mechanisms of adaptation. We review these studies: discussing EEG markers of adaptation in the frequency and the temporal domain, EEG predictors for successful adaptation and how EEG can be used to unmask latent processes resulting from adaptation, such as the modulation of spatial attention. With its high temporal resolution, EEG can be further exploited to deepen our understanding of sensorimotor adaptation.